46+(-2k)k=-2

Simple and best practice solution for 46+(-2k)k=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 46+(-2k)k=-2 equation:



46+(-2k)k=-2
We move all terms to the left:
46+(-2k)k-(-2)=0
We add all the numbers together, and all the variables
(-2k)k+48=0
We multiply parentheses
-2k^2+48=0
a = -2; b = 0; c = +48;
Δ = b2-4ac
Δ = 02-4·(-2)·48
Δ = 384
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$k_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$k_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{384}=\sqrt{64*6}=\sqrt{64}*\sqrt{6}=8\sqrt{6}$
$k_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-8\sqrt{6}}{2*-2}=\frac{0-8\sqrt{6}}{-4} =-\frac{8\sqrt{6}}{-4} =-\frac{2\sqrt{6}}{-1} $
$k_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+8\sqrt{6}}{2*-2}=\frac{0+8\sqrt{6}}{-4} =\frac{8\sqrt{6}}{-4} =\frac{2\sqrt{6}}{-1} $

See similar equations:

| -128=-4(8+3v) | | 65=2(n-4)-5(1+3n)65=2(n−4)−5(1+3n) | | -1+6x+5x+5=35 | | 4(w-3)+5=13 | | -10=7x+6(x+7) | | 7x-3+2x=7x-3 | | 3(x-2)=-4(-x+4) | | -7p+-2p=-18 | | -10=1.5c=2 | | -2+y/10=6 | | -7a+6(8a+3)=182 | | (3x-5)(x+1)=180 | | -12=-3-4m+7m | | 2(5+7p)-3=7(4p-7) | | x+6+6x-58=180 | | 1.3-x+2.1=5.7 | | b-5.73=3.27 | | 2m-3)m+1)=4(m+3) | | 12​(x−​5)=11​(x+​5) | | 148=4(1-6n) | | x+5=(x–2)–(2x–7) | | 106-11x(11x)=0 | | 10(-5x+6)-9=1+5(-10x+10) | | 4-3x+8x-4-4x=12 | | 4(3x-11)=12x | | 4x+23+10x-1=24 | | 2x-3(x+2)=5 | | 3x(4x-40)=360 | | 3x-3-3=9 | | 36p=61 | | 49-3m=4m+14* | | 99.9x=24.9 |

Equations solver categories